Desarrollo de un paquete tecnológico para la obtención de alimentos hipoalergénicos a base de lactosuero - Ambrosi, Vanina Andrea (2019)
Allergy to cow's milk is the most common food allergy in infants. Hydrolyzed hypoallergenic formulas (HIF), highly recommended for allergic babies, have virtually no immunoreactivity. Nowadays, the available evaluation methodologies are developed to detect traces of allergens. The objective of this thesis was the development of strategies, both for processing and control, to obtain a hypoallergenic food. Competitive ELISAs were designed, capable of detecting milk proteins in the analytical range required for the production of HIF. These methodologies were used to evaluate the effect of the application of different processing technologies on the antigenicity of proteins. The results showed that the hydrolysis application assisted by high hydrostatic pressure was able to decrease the antigenicity of the whey proteins in a short time of processing. The obtained hydrolysates were validated in vivo by the use of an allergic mouse model. This work allowed the design of an effective technological strategy, capable of processing whey in a short time, achieving a significant reduction in its allergenicity.